2012
DOI: 10.1038/ncomms1776
|View full text |Cite
|
Sign up to set email alerts
|

CYLD negatively regulates transforming growth factor-β-signalling via deubiquitinating Akt

Abstract: Lung injury, whether induced by infection or caustic chemicals, initiates a series of complex wound-healing responses. If uncontrolled, these responses may lead to fibrotic lung diseases and loss of function. Thus, resolution of lung injury must be tightly regulated. The key regulatory proteins required for tightly controlling the resolution of lung injury have yet to be identified. Here we show that loss of deubiquitinase CYLD led to the development of lung fibrosis in mice after infection with Streptococcus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
109
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 46 publications
5
109
0
1
Order By: Relevance
“…Graphs represent the mean + SEM. *p , 0.05, **p , 0.01, ***p , 0.001. zation (88,89). Overexpressed Smad3 can in turn transactivate the PDGF-B promoter (53), suggesting that one possible way PI3K and Smads positively cooperate for PDGF-B expression in synoviocytes is through an increase in Smad3 protein stability.…”
Section: Discussionmentioning
confidence: 99%
“…Graphs represent the mean + SEM. *p , 0.05, **p , 0.01, ***p , 0.001. zation (88,89). Overexpressed Smad3 can in turn transactivate the PDGF-B promoter (53), suggesting that one possible way PI3K and Smads positively cooperate for PDGF-B expression in synoviocytes is through an increase in Smad3 protein stability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CYLD acts as a negative regulator of the nuclear factor-κB (NF-κB) signaling pathway by deubiquitinating NF-κB essential modulator (NEMO), IκB kinase (IKK)-γ, and IKK upstream regulators, including the tumor necrosis factor (TNF), receptor-associated factor 2 (TRAF2), TRAF6, TRAF7 and receptor-interacting protein 1 (RIP1) (4)(5)(6)(7)(8)(9)(10). CYLD also regulates transforming growth factor-β (TGF-β) signaling via the deubiquitination of Akt in lung fibrosis (11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CYLD acts as a negative regulator of the nuclear factor-κB (NF-κB) signaling pathway by deubiquitinating NF-κB essential modulator (NEMO), IκB kinase (IKK)-γ, and IKK upstream regulators, including the tumor necrosis factor (TNF), receptor-associated factor 2 (TRAF2), TRAF6, TRAF7 and receptor-interacting protein 1 (RIP1) (4-10). CYLD also regulates transforming growth factor-β (TGF-β) signaling via the deubiquitination of Akt in lung fibrosis (11).Recent studies have demonstrated that CYLD deficiency may promote the development of several types of cancer in addition to skin tumors caused by mutations and loss of the heterozygosity (LOH) of CYLD. LOH of chromosome 16q, which includes the CYLD gene, has been detected in a large proportion of multiple myeloma cases and has been associated with poor overall survival (12)(13)(14).…”
mentioning
confidence: 99%
“…Therefore, it should be worth investigating the detailed functions of A20 in the canonical TGF-b pathway. A recent report indicated that CYLD decreases stability of Smad3 in a glycogen-synthase kinase3-b (GSK3b)-Hsc70-interacting protein (CHIP)-dependent manner via deubiquitinating Akt in lung fibrotic tissue and mouse lung cells, suggesting that CYLD is a negative regulator of the TGF-b-Smad pathway 52 . However, we did not observe this in CYLD-specific knockdown AML-12 cells, likely due to the differences in cellular context.…”
Section: Discussionmentioning
confidence: 99%